Investigation of inkjet printed path resistance in the context of manufacture and flexible application. Issue 1 (4th February 2019) - Tomaszewski, Grzegorz; Potencki, Jerzy; Błąd, Grzegorz; Wałach, Tadeusz; Gajór, Grzegorz; Pietrikova, Alena; Lukacs, Peter
Abstract : Purpose: The purpose of this paper is to study the repeatability of path manufacturing in the drop on demand inkjet printing process and the influences of environmental and application factors on path resistance. Design/methodology/approach: Paths were printed as multiline paths in packets one-, two- and three-layer paths on polyimide substrates using nanoparticle silver ink. The sintering conditions were determined experimentally. The paths were subjected to climatic and shock exposures and to bending processes. The resistance, profile and width of the paths were measured and analyzed. The temperature distribution for electrically heated paths was measured to identify the defects. Findings: This research shows the repeatability of printing processes and identifies the sources that cause diversification in path parameters after the whole technological process. The influence of shock, climatic and mechanical exposures on path electrical properties is indicated. An effective method for identifying defects thermally is shown. Research limitations/implications: The research could have limited universality by arbitrarily use of substrate material, ink, printhead, process parameters and kind of sample exposures. Practical implications: The research includes practically useful information about the width, thickness, defects and resistances and their changes during a typical application for a path printed with different technological parameters. Originality/value: This research presents the results of original empirical research on problems concerning the manufacture of paths with uniform parameters and shows how path parameters will change under exposures that may occur in a typical application. The research combines both production and application aspects.